“Bem menininha”: a vivência de mulheres trans* no mercado de trabalho de Mossoró - Nogueira, Lucas Castro (Universidade Federal Rural do Semi-Árido, 2018)
The present study deals with the relationship between trans* women and the labor market, understanding that, once they are part of a minority, the insertion and permanence of these women in this market presents challenging characteristics, bigger and different from those already present in daily work. In this scenario, the literature indicates that most trans* women are part of the informal market to ensure their livelihood and survival. The research, qualitative and descriptive, aimed to understand the relationship between trans* women and the labor market of Mossoró (RN), from listening to the narrative of five trans* women. For that, the semi-structured interview, mainly via WhatsApp, was used as data collection technique. The obtained data were analyzed through the technique of content analysis. Among the results discussed, we find the confirmation of the difficulty of obtaining formal jobs, even though all of them have reported working in formal markets. As far as training is concerned, all the interviewees finished High School, but only one is in the university environment. The family support they had and the possibility of schooling may have been factors that interfered in the definition of a more favorable labor reality than that of the majority of the trans* population. Regarding the meaning of work, it is observed that it is perceived in its basic form of guarantee of survival, without presenting itself as a learning factor, individual development or source of personal satisfaction. Also, among the results, the narrative of symbolic violence in daily work is highlighted. Although none of the interviewees report physical aggression or explicit verbal aggression in their work environment, there is a report of jokes, laughter and hate speech.
Monografia
Keywords: Mulheres trans*; Mossoró (RN); Mercado de trabalho; Trans* women; Mossoró (RN); Labor market; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO